(untitled) (Comparative Professional Pedagogy, 2023)
The article traces the process of teaching literacy (reading and writing) and its methods in the multilingual environment on the example of Grade 1 of general secondary education institutions in Berehovo where teaching is in the Hungarian language. Stages of the research included questionnaire in Hungarian and Ukrainian (regarding methodological support and teaching methods used to teach reading and writing in Hungarian); conducting interviews with teachers in order to get more information about the questions asked in the questionnaire. On the basis of completed questionnaires and respondents’ answers, it is established that despite the improvement of the mother tongue teaching over the last decade, the teaching of reading and writing in the official language still has more support at the methodological level. It is determined that there have also been positive developments regarding the study of the official language, as the newest primers of the Ukrainian language take into account the study of the native language and are based on it. The problem is that the use of Hungarian manuals and materials is combined with Ukrainian syllabi and curricula. It is necessary to find a comprehensive solution, because there is no need to fully integrate Hungarian textbooks into the Ukrainian educational process, it is enough to adjust them. This can be achieved by developing such syllabi that will correspond to Hungarian textbooks and manuals and at the same time take into account the peculiarities of mother tongue education for national minorities. It is substantiated that we cannot use syllabi from Hungary, firstly, because they are not officially approved in Ukraine, and, secondly, because in Hungary, learning to read and write in the Hungarian language is not interpreted as learning for a national minority. Therefore, it does not take into account peculiarities of the education of Transcarpathian Hungarians in their native language. Hungarian methodological literature used by teachers must be adapted to Ukrainian realities and requirements.